Integration of waqf-Islamic microfinance model for poverty reduction: the case of Bangladesh - Haneef, Mohamed Aslam; Pramanik, Ataul Huq; Mohammed, Mustafa Omar; Muhammad, Aliyu Dahiru; Amin, Fouad M (Emerald Group Publishing, 2015)
Purpose – This paper aims to develop an integrated waqf-based Islamic microfinance (IsMF) for poverty reduction in Bangladesh. Microfinance institutions (MFIs) have been constrained by the high cost of funds, high interest rate charges and poor human resource quality of the recipients. Islamic MFIs have recently evolved with the hope of overcoming these financial, ethical and human capital deficiencies faced by the conventional financial institutions. Moreover, a good number of integrated models have been proposed to enhance the role played by Islamic MFIs. Most of these models, however, lack empirical justifications. Design/methodology/approach – The research uses survey techniques. A total of 381 respondents were included in the survey. The integrated waqf-based Islamic microfinance model (IWIMM) was earlier on developed using literature and intellectual discussions. There are six constructs presenting the IWIMM, namely, waqf resources, IsMF, takaful, project financing, human resource development and poverty alleviation. In the survey instrument, 45 items represent the six constructs, but only 26 items have been retained after factor analysis. Structural equation modelling has been adopted to examine the relationship among the constructs. Findings – The results show that there are significant relationships between IsMF and takaful, waqf resources and human resource development, takaful and human resource development, IsMF and human resource development and, waqf resources and project financing. The results also indicate that poverty alleviation is possible through the integration of these constructs. Research limitations/implications – Though the paper has studied conventional and Islamic MFIs in Bangladesh, one of the populated Organisation of Islamic Cooperation (OIC) member countries and also where poverty incidence is high, further studies need to be conducted in other OIC member countries to adopt the model in line with practical and regulatory environment of those countries. Similarly, the study is based on the perception of the respondents, which limits the generalization of the result. Practical implications – The paper proposed a model that has the potential of being applied for poverty alleviation programmes in most of the OIC member states. Originality/value – The present paper has developed an IWIMM for poverty reduction.